Comics as Communication - Davies, Paul Fisher. author. aut Link
XIX, 338 p. 60 illus., 20 illus. in color.
Keywords: This book explores how comics function to make meanings in the manner of a language. It outlines a framework for describing the resources and practices of comics creation and readership, using an approach that is compatible with similar descriptions of linguistic and multimodal communication. The approach is based largely on the work of Michael Halliday, drawing also on the pragmatics of Paul Grice, the Text World Theory of Paul Werth and Joanna Gavins, and ideas from art theory, psychology and narratology. This brings a broad Hallidayan framework of multimodal analysis to comics scholarship, and plays a part in extending that tradition of multimodal linguistics to graphic narrative.